Maternal fructose drives placental uric acid production leading to adverse fetal outcomes - Asghar, Zeenat A. (Sci Rep, 2016)
Maternal metabolic diseases increase offspring risk for low birth weight and cardiometabolic diseases in adulthood. Excess fructose consumption may confer metabolic risks for both women and their offspring. However, the direct consequences of fructose intake per se are unknown. We assessed the impact of a maternal high-fructose diet on the fetal-placental unit in mice in the absence of metabolic syndrome and determined the association between maternal serum fructose and placental uric acid levels in humans. In mice, maternal fructose consumption led to placental inefficiency, fetal growth restriction, elevated fetal serum glucose and triglyceride levels. In the placenta, fructose induced de novo uric acid synthesis by activating the activities of the enzymes AMP deaminase and xanthine oxidase. Moreover, the placentas had increased lipids and altered expression of genes that control oxidative stress. Treatment of mothers with the xanthine oxidase inhibitor allopurinol reduced placental uric acid levels, prevented placental inefficiency, and improved fetal weights and serum triglycerides. Finally, in 18 women delivering at term, maternal serum fructose levels significantly correlated with placental uric acid levels. These findings suggest that in mice, excess maternal fructose consumption impairs placental function via a xanthine oxidase/uric acid-dependent mechanism, and similar effects may occur in humans.